The relations between technological knowledge, pedagogical knowledge, and inventive skills among Malay language teachers - Ahmad Kusaini, Ezwafahmey; Mahamod, Zamri; Wan Mohammad, Wan Muna Ruzanna (LPMPP Universitas Negeri Yogyakarta, 2024)
Through the use of technology in the classroom, teachers can improve their ability to deliver effective and relevant content. Teachers should be more prepared to apply this technology to ensure that students will have more fun and have a high interest in continuing to learn in the era of globalization which is based on the use of these information communication technology elements in the classroom during the teaching and facilitation process. Thus, this study was to identify the relationship between technological knowledge, technological content knowledge, technological pedagogical knowledge, technological pedagogical content knowledge, and inventive skills for teachers. The questionnaire was distributed to 400 teachers who teach Malay language subjects at Secondary schools in Malaysia. To test the hypothesis, the structural equation using a PLS-SEM framework was used. The results showed that technological knowledge, technological content knowledge, technological pedagogical knowledge, and technological pedagogical content knowledge have a positive relationship with inventive skills for teachers.